Tractolira delli, a new Volutidae (Mollusca: Gastropoda: Neogastropoda) from the abyssal plains off Antarctica - Leal, José H.; Harasewych, M. G. (Zootaxa, 2005)
A new deep-sea species of Volutidae in the genus Tractolira is named from material collected by the United States Antarctic Program in and around the Ross Sea, eastern Antarctica, and from one locality in the Subantarctic region. Tractolira delli new species is most similar to T. sparta Dall, 1896, from which it differs in having a relatively wider shell, less prominent spiral sculpture, with narrower threads, and by the absence of strong axial ribs at least on the first three teleoconch whorls. The other Antarctic congener, Tractolira germonae, has a thicker, dark-brown periostracum (instead of a thin, light-yellow one), a proportionally smaller inductura, and lacks surface sculpture.